Effect of Recreational Activities on Mathematics Achievement and Self-Efficacy of Students with Mild Intellectual Disabilities in an Inclusive Classroom in Calabar Metropolis, Cross River State, Nigeria - Ibok, Ekpenyong Effiong; Anam, Blessing Bassey; Akpa, Stephen Ushie; Ekon, Esther Etop; Obeten, Okoi Okorn; Ogar, Raymond Ogbebe; Inah, Lovina Idoko; Unamba, Chioma Precious; Obi, Joy Joseph; Amos, Paul Imeh; Edet, Itam Ben; Swem, Terfa; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2026)
Aims: The research work looked at the effect of recreational activities on Mathematics achievement and self-efficacy of students with mild intellectual disabilities attending an inclusive classroom in Calabar Metropolis of Cross River State, Nigeria. The research objectives were identified to guide the investigation. Two research questions were developed, each of which was transformed into a null hypothesis. A literature review of the study variables was conducted, and research gaps were outlined. Method: The study design was a 2x2 factorial. The design was quasi-experimental and non-random. A sample of 120 students with mild disabilities (60 students were taught using recreational activities, identified on one hand, while another set of 60 were randomly selected and received teaching through the traditional method) in SSI classes within Calabar Metropolis, Cross River State, Nigeria. Data collection was based on a mathematical Achievement Test (MAT) and a Mathematics Self-Efficacy Rating Scale questionnaire (MSERSQ). The research design is based on two hypotheses. Reliability of the SES was assessed using Cronbach's alpha. 88, and the MAT reliability was calculated using the Kuder-Richardson formula 20 (KR-20), which gives an index of. 86. Descriptive statistics were employed to answer research questions, and Analysis of Covariance (ANCOVA) was employed to test the null hypotheses. Results: The results of the analysis using ANCOVA revealed that mild intellectual disabilities students had performed better in mathematics achievement when they were tutored with recreational activities than those who received tutoring with traditional approach (F-ratio = 165.140, p<.050), with partial eta squared of 0.585 (moderate effect) and self-efficacy (F-ratio= 724.919, p<.050) with partial eta squared of .862 indicating high effect. Conclusion: The study concluded that high academic achievement and self-efficacy of students with mild intellectual disabilities depend on the level of effective participation in recreation activities involving teachers in the teaching of mathematics concepts.